Factors affecting employee job satisfaction: A comparative study of conventional and Islamic insurance - Khalil-Ur Rahman; Waheed Akhter; Saad Ullah Khan (Cogent Business & Management, 2017)
This paper attempts to investigate the factors that affect job satisfaction of sales agents from Islamic (Hereafter; Takāful) and conventional insurance of Pakistan using Herzberg two-factor motivation theory. Using multi-stage stratified random sampling, we received a total of 318 usable responses (185 from family Takāful and 133 from life insurance). A multiple regression and hierarchal regression model including 11 hygiene–motivational factors were used to examine job satisfaction in the presence of moderating factor Shari'ah perception. The outcomes regarding Herzberg two-factor theory were entirely distinctive between those two direct sales groups with the presence of moderating variable Shari'ah perception. Without moderating the effect of Shari'ah perception, family Takāful and conventional life insurance full-time direct sales agents demonstrated that hygiene factors and motivational factors were both more effective indicators of job satisfaction in Pakistani context. While checking the moderating effect in the presence of moderating variable Shari'ah perception, family Takāful sales agents are satisfied with hygiene factors where the motivators are not significantly affected by Shari'ah perception. On the other hand, conventional life insurance sales agents have no concern with Shari'ah perception.
Keywords: 650